2018
DOI: 10.1001/jamanetworkopen.2018.5293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated With Patient Nondisclosure of Medically Relevant Information to Clinicians

Abstract: Key Points Question What medically relevant information do patients withhold from their clinicians, and why do they do so? Findings In 2 national, nonprobability online surveys of 4510 US adults, most participants reported withholding at least 1 of 7 types of medically relevant information, especially when they disagreed with the clinician’s recommendations or misunderstood the clinician’s instructions. The most commonly reported reasons for not disclosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
115
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 10 publications
4
115
1
3
Order By: Relevance
“…Failure of the patient to disclose medically relevant information to clinicians can also impair care or even lead to harm. 11 Uncomfortable conversations may often be avoided, and patients may not be honest with their physicians. In fact, 60% to 80% of people in a recent study reported that they had withheld or lied to their health care provider about medically relevant information.…”
mentioning
confidence: 99%
“…Failure of the patient to disclose medically relevant information to clinicians can also impair care or even lead to harm. 11 Uncomfortable conversations may often be avoided, and patients may not be honest with their physicians. In fact, 60% to 80% of people in a recent study reported that they had withheld or lied to their health care provider about medically relevant information.…”
mentioning
confidence: 99%
“…Patients commonly withhold medically relevant information from their physicians, a pattern that likely hinders the quality of care. 34 Patient activation or engagement is associated with positive clinical and healthcare utilization outcomes. 35 Patient-mediated implementation interventions showed a positive impact on patient knowledge, decision making, communication, and behavior.…”
Section: Social Influencesmentioning
confidence: 99%
“…A recent study has shown the level of non-disclosure of medically relevant information to healthcare professionals [3]. Using data from several online surveys, people were asked if they ever withheld information from healthcare professionals and why.…”
Section: Non-disclosure Of Medically Relevant Informationmentioning
confidence: 99%